Stimulus control with fixed-ratio reinforcement - Zeiler, Michael D. (1968)
Pigeons were trained on a three-stimulus simultaneous discrimination with reinforcements given on fixed-ratio schedules ranging from one response per reinforcement to 205 responses per reinforcement. Responses to any of the three stimuli advanced the ratio, but, when it was completed, a reinforcement followed a response to one designated stimulus. Throughout the ratio, the birds responded mainly to the designated stimulus. The relatively few responses to the other stimuli usually occurred immediately after postreinforcement pauses. The distribution of responses to the various stimuli was not affected by omitting reinforcements.